High gravity enzymatic hydrolysis of hydrothermal and ultrasonic pretreated big bluestem with recycling prehydrolysate water. (December 2017) - Xu, Youjie; Zhang, Ke; Wang, Donghai
Abstract: Enhancing sugar concentration and minimizing water consumption are key objectives for future cellulosic biofuel economics. To achieve those objectives, high-solids loading pretreatment and enzymatic hydrolysis (up to 20%, w/v) were studied. Big bluestem was selected and combined hydrothermal and ultrasonic treatment without chemicals addition was carried out in this study. Optimal high-solids loading pretreatment (16%, w/v) was identified in the ultrasonic reactor at 200 °C for 30 min. High-solids enzymatic hydrolysis (12%, w/v) was inefficient in the laboratory rotary shaker. However, using a horizontal reactor with good mixing is effective for high solids loading (20%, w/v), yielding 75 g/L of glucose. Minimum water to detoxify pretreated biomass while maintaining high sugar yields was 10 mL/g, which reduced by 50% as compared to the conventional washing process for steam-treated wheat straw. Recycling pretreatment liquor to treat the next batch of biomass was proved to be feasible without affecting the sugar yields. Highlights: High-solids biomass (16%, w/v) treatment was carried out using combined hydrothermal and ultrasonic reactor. High-solids enzymatic hydrolysis (20%, w/v) was studied using horizontal reactor with good mixing. High glucose concentration (75 g/L) and glucose yield of 72%.were achieved. Minimizing washing water and using recycling pretreatment liquor to increase water efficiency.